Function of Serum Complement in Drinking Water Arsenic Toxicity - Laila N. Islam; M. Shamim Hasan Zahid; A. H. M. Nurun Nabi; Mahmud Hossain (Journal of Toxicology)
Serum complement function was evaluated in 125 affected subjects suffering from drinking water arsenic toxicity. Their mean duration of exposure was 7.4±5.3 yrs, and the levels of arsenic in drinking water and urine samples were 216±211 and 223±302 μg/L, respectively. The mean bactericidal activity of complement from the arsenic patients was 92% and that in the unexposed controls was 99% (P<0.01), but heat-inactivated serum showed slightly elevated activity than in controls. In patients, the mean complement C3 was 1.56 g/L, and C4 was 0.29 g/L compared to 1.68 g/L and 0.25 g/L, respectively, in the controls. The mean IgG in the arsenic patients was 24.3 g/L that was highly significantly elevated (P<0.001). Arsenic patients showed a significant direct correlation between C3 and bactericidal activity (P=0.014). Elevated levels of C4 indicated underutilization and possibly impaired activity of the classical complement pathway. We conclude reduced function of serum complement in drinking water arsenic toxicity.